Ferroelectric/piezoelectric materials in energy harvesting: Physical properties and current status of applications - Karageorgou, M.-A.; K. L. Tsakmakidis; Stamopoulos, D. (Crystals, 2024)
The inevitable feedback between the environmental and energy crisis within the next decades can probably trigger and/or promote a global imbalance in both financial and public health terms. To handle this difficult situation, in the last decades, many different classes of materials have been recruited to assist in the management, production, and storage of so-called clean energy. Probably, ferromagnets, superconductors and ferroelectric/piezoelectric materials stand at the frontline of applications that relate to clean energy. For instance, ferromagnets are usually employed in wind turbines, superconductors are commonly used in storage facilities and ferroelectric/piezoelectric materials are employed for the harvesting of stray energy from the ambient environment. In this work, we focus on the wide family of ferroelectric/piezoelectric materials, reviewing their physical properties in close connection to their application in the field of clean energy. Among other compounds, we focus on the archetypal compound Pb(Zr,Ti)O3 (or PZT), which is well studied and thus preferred for its reliable performance in applications. Also, we pay special attention to the advanced ferroelectric relaxor compound (1−x)Pb(Mg1/3Nb2/3)O3−xPbTiO3 (or PMN-xPT) due to its superior performance. The inhomogeneous composition that many kinds of such materials exhibit at the so-called morphotropic phase boundary is reviewed in connection to possible advantages that it may bring when applications are considered.